Development and Technical Adequacy of the District Capacity Assessment. (April 2022) - Ward, Caryn S.; Harms, Anna L.; St. Martin, Kim; Cusumano, Dale; Russell, Christine; Horner, Robert H.
The purpose of this article is to describe the methods and results used to establish the district capacity assessment's (DCA) content validity, response process validity, construct validity, internal consistency, and test–retest reliability. The DCA measures a district's ability to support school-level implementation of evidence-based practices (EBPs). Assessment results are then used to guide action planning. The DCA is grounded in the understanding that districts must develop knowledge and skills in the use of implementation science methods if they are to support successful use of an innovation. Specifically, three studies were conducted. The first study established the DCA's content validity, that is, the extent to which the DCA represents constructs comprising district-level implementation capacity. The second study established the DCA's internal structure, or the relationships among the items compared to the constructs being measured and how well the items measured the same construct. The third and final study assessed how the results of the DCA varied over time, thus establishing the instrument's test–retest reliability. District Implementation Teams, researchers, or facilitators who use the DCA can be confident that the assessment is founded on research drawing from implementation science practices and methods.